The insecticidal spider toxin SFI1 is a knottin peptide that blocks the pore of insect voltage‐gated sodium channels via a large β‐hairpin loop. (23rd January 2015) - Bende, Niraj S.; Dziemborowicz, Sławomir; Herzig, Volker; Ramanujam, Venkatraman; Brown, Geoffrey W.; Bosmans, Frank; Nicholson, Graham M.; King, Glenn F.; Mobli, Mehdi
<x xml:space="preserve">Abstract</x> Spider venoms contain a plethora of insecticidal peptides that act on neuronal ion channels and receptors. Because of their high specificity, potency and stability, these peptides have attracted much attention as potential environmentally friendly insecticides. Although many insecticidal spider venom peptides have been isolated, the molecular target, mode of action and structure of only a small minority have been explored. Sf1a, a 46‐residue peptide isolated from the venom of the tube‐web spider Segesteria florentina, is insecticidal to a wide range of insects, but nontoxic to vertebrates. In order to investigate its structure and mode of action, we developed an efficient bacterial expression system for the production of Sf1a. We determined a high‐resolution solution structure of Sf1a using multidimensional 3D/4D NMR spectroscopy. This revealed that Sf1a is a knottin peptide with an unusually large β‐hairpin loop that accounts for a third of the peptide length. This loop is delimited by a fourth disulfide bond that is not commonly found in knottin peptides. We showed, through mutagenesis, that this large loop is functionally critical for insecticidal activity. Sf1a was further shown to be a selective inhibitor of insect voltage‐gated sodium channels, consistent with its 'depressant' paralytic phenotype in insects. However, in contrast to the majority of spider‐derived sodium channel toxins that function as gating modifiers via interaction with one or more of the voltage‐sensor domains, Sf1a appears to act as a pore blocker.